Single-cell RNA sequencing analysis of shrimp immune cells identifies macrophage-like phagocytes - Yang, Peng; Chen, Yaohui; Huang, Zhiqi; Xia, Huidan; Cheng, Ling; Wu, Hao; Zhang, Yueling; Wang, Fan (eLife, 2022)
Despite the importance of innate immunity in invertebrates, the diversity and function of innate immune cells in invertebrates are largely unknown. Using single-cell RNA-seq, we identified prohemocytes, monocytic hemocytes, and granulocytes as the three major cell-types in the white shrimp hemolymph. Our results identified a novel macrophage-like subset called monocytic hemocytes 2 (MH2) defined by the expression of certain marker genes, including Nlrp3 and Casp1 . This subtype of shrimp hemocytes is phagocytic and expresses markers that indicate some conservation with mammalian macrophages. Combined, our work resolves the heterogenicity of hemocytes in a very economically important aquatic species and identifies a novel innate immune cell subset that is likely a critical player in the immune responses of shrimp to threatening infectious diseases affecting this industry.